NUTRITION ASSISTANCE PROGRAM EFFECT ON WEIGHT OF CHILDREN UNDER FIVE YEARS - Tri Handari, Siti Riptifah; Fauziah, Munaya; Asmalasari, Mia Endah (Universitas Ahmad Dahlan, 2014)
Background:Nutrition is a major factor in improving the quality of human resources (HR). The quality of a countrys human resources can be measure with nutritional status of children under five year, which is the candidate for the next of the nation generation. Under nutrition rates among children under five in Indonesia according Riskesdas 2007 is 18.4% (prevalence of severe undernutrition children underfive is 5.4% and 13.0% of children underfive undernutrition) and data Riskesdas 2010 is 17.9% (prevalence of severe undernutrition children under five 4.9% and 13.0% of children under five undernutrition. Although the figure has decreased, but the number is still high and has not reached the MDG target of 15.5% and RPJMN 2010-2014 is 15%. Widespread malnutrition in the community due to multifactorial, but there are two reasons that are believed to be the direct cause of low consumption of food and the presence of infectious disease. The indirect causes are factors of parenting and childcare, food availability also environmental sanitation.Method: This study aims to determine the effect of nutrition assistance programs during one month of the weight of children under five. The method used is Non-Randomized Quasi- Experiment with pre-test and post-test group.Â Sampling was conducted with a purposive sample of experiments, a total of 15 samples.Result: Results of Paired T-Test showed that the value of p<0.005 (p = 0.001). It can be concluded that the nutritional assistance program, which lasted for one month is able to increase weight children under five (p = 0.001).Conclusion: Advice for PHC/Health Department to address the nutritional problems in children under five is to increase nutrition assistance program through nutritional care of the family.Â Keyword: nutrition assistance program, weight, children under five years